SARS-CoV-2 transmission associated with high school wrestling tournaments — Florida, December 2020-January 2021 - Atherstone, C.; Siegel, M.; Schmitt-Matzen, E.; Sjoblom, S.; Jackson, J.; Blackmore, C.; Neatherlin, J. (Morbidity and Mortality Weekly Report (MMWR), 2021)
On December 7, 2020, local public health officials in Florida county A were notified of a person with an antigen-positive SARS-CoV-2 test* result who had attended two high school wrestling tournaments held in the county on December 4 and 5. The tournaments included 10 participating high schools from three counties. The host school (school A in county A) participated in the tournaments on both days; five high school teams from two counties participated the first day only; four additional high school teams from the three counties participated the second day. A total of 130 wrestlers, coaches, and referees attended the tournaments (Table). During December 8-9, 13 wrestlers from school A received positive SARS-CoV-2 test results (Figure), including nine who were symptomatic, two who were asymptomatic, and two for whom symptom status at time of specimen collection was unknown. Local public health officials in the three counties initiated an investigation† and tested specimens from an additional 40 attendees from nine of the 10 participating schools. A total of 54 (41.5%) of the 130 tournament attendees received testing, and 38 cases of SARS-CoV-2 infection were identified; the minimum attack rate was 30.2% (38 of 126§), and 70.4% (38 of 54) of tests had a positive result. Among contacts of the 38 COVID-19 patients, 446 were determined by investigators to meet the CDC definition of a close contact, including 62 who were household contacts and 384 who were in-school contacts (classmates, teachers, noncompeting wrestling team members, and other school athletic team members). Among these 446 contacts, five had received a diagnosis of COVID-19 during June-November and were excluded from attack rate calculations. Among 95 (21.3%) contacts who received SARS-CoV-2 testing, 41 (43.2%) received a positive test result (minimum attack rate = 9.3% [41 of 441]); 21 (51.2%) persons with positive test results were symptomatic, eight (19.5%) were asymptomatic, and symptom status for 12 (29.3%) was unknown at the time of specimen collection. Among contacts, attack rates were highest among household members (30.0%) and wrestling team members who did not attend the tournament (20.3%), as were the percentages of positive test results (60.0% among household members and 54.2% among team members). Among all contacts, the odds of receiving a positive test result were highest among household contacts (odds ratio = 2.7; 95% confidence interval = 1.2-6.0). Local health authorities reported the death of one adult contact aged >50 years.